Various dimensions of legal liability - Zalewska, Monika (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
The legal liability is the issue of vast complexity and hence worth to analyze both on theoretical and practical level. The main goal is to analyze of one of the understandings of legal responsibility, imputation, proposed by Hans Kelsen. Therefore, first the concept of imputation will be described. Secondly, the mechanism will be revealed, which transforms imputation into legal responsibility. The conclusion includes the notion of incompleteness of Pure Theory of Law in application of law field.